Nikolai Klyuev’s Epistolary Review of Sergei Yesenin’s Poem ‘Pugachev’: “Dark Places” of Multidimensional Evaluation - S. N. Pyatkin; I. V. Kudryashov (Научный диалог)
This article presents a historical and literary analysis of the epistolary review by the peasant poet Nikolai Klyuev (1884—1937) of the dramatic poem ‘Pugachev’ (1922) by S. A. Yesenin. The review, contained in a letter dated January 28, 1922, has been characterized in literary studies as an “enthusiastic greeting.” However, the authors argue that Klyuev’s evaluation of Yesenin’s poem contains “dark places,” specifically his deliberate omission of the imagist poetics of ‘Pugachev’ and his seemingly unmotivated comparison of Yesenin’s dramatic poem with Pushkin’s tragedy ‘Boris Godunov’. The authors demonstrate that Klyuev believed that ‘Pugachev’, which reflects Yesenin’s rapid growth as a poet, was the result of his connection to the traditions of folk poetry rather than the product of the imagist school. Klyuev’s judgment that Yesenin’s poem was “more necessary and desirable than ‘Boris Godunov’” may appear illogical and paradoxical at first glance, but the authors emphasize that his epistolary review expresses only his personal relationship with the younger poet and does not evaluate the literary merits of the two works. The book ‘Pugachev’, which was sent to Vytegra along with the letter, became a sign of trust from the donor, a gift, a tangible expression of love and friendship from the addressee, and evidence of the spiritual and creative devotion of the student to his teacher. For Klyuev, who sought to restore his relationship with Yesenin, ‘Pugachev’ was “more necessary and desirable” because its content resonated with the idea of sacrificial service to his people, which is a recurring theme in Klyuev’s work.